Preparation and Use of Rock Phosphate and waste mica enriched compost as fertilizer - Meena, M.D.; Biswas, D.R. (Indian Farming, 2015)
Enriched compost is prepared using rice straw, low grade rock phosphate, waste mica and Aspergillus awamori. Application of enriched compost results in improved physical, chemical and biological properties of soils. Enriched compost helps in enhancing mobilization of unavailable P and K in rock phosphate and waste mica into their available forms and thus improves the quality of compost in terms of its total P, K, Ca, Mg, and micronutrient contents. Enriched compost is a longterm source of nutrients, which are readily available to the plants.Enriched compost could be an alternative option for sustainable management of agricultural wastes and a potential avenue for utilization of low-grade resources like rock phosphate and waste mica into a value added organic product for sustainable crop production and maintaining soil fertility which could substitute half of the water soluble fertilizers demand. Enriched compost has a great potential to improve health and quality of neutral to alkaline soil as well as salt-affected soils, which need to explore in future.